New Institutional Theory to Assess Corruption in Malaysia’s Civil Service - Farhana; Ahmad Faiz Yaakob; Tunku Nashril Tunku Abaidah (International Journal of Asia Pacific Studies, 2026)
Corruption remains a central concern in bureaucratic and political research. Traditionally, scholarship has focused predominantly on corruption’s economic and legal dimensions. This study asks how cultural norms interact with institutional frameworks to sustain or resist corruption in Malaysia’s civil service. It proceeds from two core propositions: first, that institutions actively shape cultural attitudes towards corruption; and second, that pre-existing cultural norms influence how institutions tolerate or reject corrupt practices. While new institutional theory (NIT) has been extensively applied in global corruption studies, its application in the Malaysian context, particularly to understand how culture sustains corruption within the civil service, remains limited. This study addresses this gap by analysing qualitative data from sixteen in-depth interviews with public officials and policy experts. Findings reveal that corruption in Malaysia often transcends simple rule-breaking, instead it becomes embedded in cultural logics of reciprocity, survival, and social obligation. This study highlights one of the first systematic applications of NIT to Malaysia’s civil service by positioning cultural norms as co-productive with formal institutions to bridge the gap between predominantly legal-economic explanations and culturally grounded interpretations. This study posits that recognising the dual influence of formal and informal institutions is essential for designing reforms that are not only legally robust but also culturally resonant.